Design of Stacked Patch Antenna using LTCC technology / Zatul Iffah Abd Latiff - Abd Latiff, Zatul Iffah (2013)
This project presents the design of Stacked Patch Antenna using the LTCC technology with aperture coupler as the feeding technique. The proposed design was simulated using CST Microwave Studio software based on operating frequency of 5.8 GHz. The advantages of LTCC technology over the PCB technology are observed and output from the result shows that LTCC technology is better that PCB technology with 88% improvement in term of gain and 75.9% improvement on the antenna size. A comprehensive study focusing on the optimization of the antenna performance was done to understand the effect of various dimensional parameters towards the antenna. The results were analysed and discussed in term of radiation pattern, gain, return loss, resonant frequency and antenna size.